Emodin protects against severe acute pancreatitis-associated acute lung injury by activating Nrf2/HO-1/GPX4 signal and inhibiting ferroptosis in vivo and in vitro - Gang Shen; Haiyun Wen; Huijuan Li; Xuetao Zhang; Bowen Lan; Xuanchi Dong; Peng Ge; Yalan Luo; Hailong Chen (BMC Gastroenterology, 2025)
Abstract Background Severe acute pancreatitis (SAP) has high morbidity, a complicated and dangerous course, and many complications, including severe pulmonary complications. SAP-associated acute lung injury (SAP-ALI) is still a significant challenge for surgeons because of its high mortality. Therefore, more effective treatment methods are urgently needed. Emodin (EMO) has shown tremendous potential in treating many refractory diseases. However, its protection mechanism in SAP-ALI needs to be further clarified. This study was undertaken to investigate the protective effects of EMO against lung injury in SAP rats and alveolar epithelial cells, with a particular focus on the classical ferroptosis pathway. Methods In an in vivo study, forty SD rats were evenly split into five groups: sham operation (SO) group, the biliopancreatic duct was retrogradely injected with 5% sodium taurocholate (STC) to create the SAP group, SAP + EMO group was administered EMO via gavage to the rats following the modeling, SAP + ML385 group (a given inhibitor of nuclear factor erythroid 2-related factor 2 (Nrf2)), SAP + ML385 + EMO group. In an in vitro study, alveolar epithelial A549 cell lines were exposed to lipopolysaccharide (LPS) and treated with EMO. ML385 was also used to inhibit the expression of Nrf2. Pancreatic and lung tissue damage was evaluated using histological examination and molecular experiments. Enzyme-linked immunosorbent assays (ELISA) were used to assess the levels of pro-inflammatory cytokines, Fe2+, and associated oxidative stress indicators in the serum and cell supernatant. Real-time polymerase chain reaction (PCR), Western blot (WB), and immunofluorescence were used to find the expressions of related mRNAs and proteins in the lung tissue or A549 cells. Results The findings demonstrated that suppressing Nrf2 expression exacerbated the inflammatory response brought on by SAP and the pathological alterations of SAP-ALI. Emodin treatment reversed this pathological change by activating the Nrf2/Heme Oxygenase-1 (HO-1)/glutathione peroxidase 4 (GPX4) signal path. Moreover, these results also showed that EMO, contrary to the effects of ML385, suppressed the ferroptosis response, which manifested as up-regulated glutathione (GSH) and GPX4 levels in vivo and in vitro and down-regulated malondialdehyde (MDA), superoxide dismutase (SOD), Fe2+, and reactive oxygen species (ROS) levels. Conclusions Our results demonstrated that EMO effectively inhibited ferroptosis both in vivo and in vitro, while also modulating the Nrf2/HO-1/GPX4 signaling pathway to provide protection against SAP-ALI.